Episodios cardiovasculares en pacientes con insuficiencia renal oculta detectada mediante fórmulas de filtrado glomerular - Calvo Hueros, Juan Ignacio (Aten Primaria, 2008)
OBJECTIVE: The objective of this work was to value the relationship between cardiovascular disease and presence of hidden renal failure in patients between 35 and 74 years followed up for 10 years. DESIGN: Observational, longitudinal, retrospective study of a cohort of patients. SETTING: Primary care health centre. PARTICIPANTS: We studied 875 patients (average age, 55.6 years, with 57.4% women) without evidence of cardiovascular disease, cared for in an urban primary health centre. MEASUREMENTS AND MAIN RESULTS: Glomerular filtration was estimated using Cockcroft-Gault and simplified MDRD equations. Hidden renal failure was considered if the glomerular filtration was <60 mL/min with a normal serum creatinine concentration. Using the Cockcroft-Gault equation 11.2% of study population had hidden renal failure and 12% when using MDRD, and 16.3% of patients with hidden renal failure using Cockcroft-Gault equation had coronary events. The relative risk in this group was 1.8 (95% confidence interval [CI], 1.1-2.9; P<.05). The percentage of coronary events was 16.2% when glomerular filtration was estimated by MDRD (relative risk, 1.9; 95% CI, 1.2-3.1; P<.05). Binary logistic regression analysis showed that age, male sex, smoking, diabetes, and diastolic pressure were the predicting variables of cardiovascular events, the highest odds ratio corresponding to the smoking population. The presence of hidden renal failure was not statistically significant using either Cockcroft (odds ratio, 1.21; 95% CI, 0.64- 2.28; P=.566) or MDRD (odds ratio, 1.64; 95% CI, 0.77-3.48; P=.200). CONCLUSIONS: The prevalence of occult renal dysfunction in the 35-74 years population is high, but it does not behave as an independent cardiovascular risk factor.